متحولات النوى التي تتفكك بإصدار جسيمات والمتحولات الكونية (Latakia University Journal -Basic Sciences Series, 2018)
تم في هذا العمل المقدم دراسة النوى المصدرة لـ، وربط متحولاتها بعضها ببعض وبالمتحولات الكونية. ومن خلال هذه الدراسة تم التحقق من أن قيم ثوابت علاقات الربط هذه تختلف من عنصر لآخر وتختلف كذلك إشارات هذه الثوابت من مجال لقيم العدد الذري ( Z ) لآخر. لقد أمكن أيضاً من خلال هذه الدراسة الحصول على بعض المعلومات حول تاريخ تشكل النوى والحد الأعلى للأعداد الذرية للعناصر التي يمكن أن تتشكل طبيعياً في كل مرحلة وربط ذلك بالتاريخ الحراري للكون ولسرعة الضوء المتغيرة، وتم كذلك تحديد الحد الأعلى للأعداد الذرية للعناصر التي يمكن الحصول عليها صنعياً.   In this work, the nuclei that emits - particles have been studied, and their variables have been correlated with each other and with the cosmic variables. This study proved that the values of the constants of this correlating relation differ from one element to another, and the signs of these constants also differ from one medium of atomic number amounts to another. The study shows it is possible to get some information about the history of the creating of nuclei, and about the maximum value of the atomic number of elements. These can naturally be created in each phase, and correlated that with thermal history of the cosmos and with the variant speed of light. It was also determined the maximum value of the atomic number of elements can be artificially obtained.